Urban disorder in democratic transitions: Ukraine’s municipal policing debates in comparative perspective - Light, Matthew (Policing and society, 2025)
The paper examines debates on police decentralisation in Ukraine since 2014, when Russia first attacked Ukraine and the country began a democratic transition, through February 2022, when the current full-scale invasion began. Although Ukraine’s constitution gives no policing authority to local governments, municipalities have created their own de facto local policing services, ‘municipal guards.’ In Ukraine, unlike nearly all other post-Soviet states, war and democratic transition have brought onto the political agenda debates about policing decentralisation for urban public order, incivilities, and property rights. Previous studies of post-authoritarian police reform have neglected such debates, focusing on criminal law and human rights. We argue that clarifying the role of local authorities in controlling public order is key to the success of police reform and should receive greater political and scholarly attention. Indeed, there is a strong case that ‘democratic policing’ in modern states requires some local control of public order.